THE EFFECT OF DIFFERENT QUALITY PELLETED FEEDS ON THE GROWTH OF GREEN CATFISH (Hemibagrus nemurus) IN FLOATING NET CAGE - Ningrum Suhenda; Reza Samsudin; Estu Nugroho; Anang Hari Kristanto (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2010)
The study was conducted to evaluate the different protein content of fish feed on the growth performance of green catfish (Hemibagrus nemurus). Two thousand fingerlings averaging 3.92±0.32 g of individual body weight were stocked in each floating net cage (3 m x 3 m x 3 m) in Musi River, South Sumatra. They were fed daily for four months with feed protein content of 27% and 31%. The feed was given in pelleted form at 4%-8% of the total body weight. The result showed that the feed with 31% protein content gave better performance and significant different (P<0.05) than 27% protein feed. The feed content 31% protein was optimum for green catfish fingerlings and gave higher average individual weight gain (80.48 g), specific growth rate (2.67%), fat retention (29.48%) and better feed conversion ratio (2.28). Survival rates were the same for 2 treatments and ranged between 94.17%-95.18%.